1992
DOI: 10.1136/hrt.67.1.57
|View full text |Cite
|
Sign up to set email alerts
|

"Subclinical" pacemaker syndrome: a randomised study of symptom free patients with ventricular demand (VVI) pacemakers upgraded to dual chamber devices.

Abstract: Most patients who were satisfied with long term pacing in VVI mode benefited from upgrading to DDD mode pacing suggesting the existence of "subclinical" pacemaker syndrome in up to 75% of such patients. The DDI mode offered little subjective or objective benefit over VVI mode in this population and should be reserved for patients with paroxysmal atrial arrhythmias. VVI mode pacing should be used only for patients with very intermittent symptomatic bradycardia or atrial fibrillation with a good chronotropic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 34 publications
(8 reference statements)
1
43
0
Order By: Relevance
“…1 Some studies have suggested that as compared with patients with ventricular pacemakers, those with dual-chamber pacemakers have a better healthrelated quality of life. 2,3 However, those small, crossover studies have had inconsistent blinding, have occasionally used nonstandard means to measure quality of life, and have been unable to assess whether improvements in the quality of life are maintained during long-term follow-up. The purpose of the Pacemaker Selection in the Elderly trial was to assess the effect of the pacing mode on the long-term health-related quality of life of elderly patients with pacemakers.…”
Section: Discussionmentioning
confidence: 99%
“…1 Some studies have suggested that as compared with patients with ventricular pacemakers, those with dual-chamber pacemakers have a better healthrelated quality of life. 2,3 However, those small, crossover studies have had inconsistent blinding, have occasionally used nonstandard means to measure quality of life, and have been unable to assess whether improvements in the quality of life are maintained during long-term follow-up. The purpose of the Pacemaker Selection in the Elderly trial was to assess the effect of the pacing mode on the long-term health-related quality of life of elderly patients with pacemakers.…”
Section: Discussionmentioning
confidence: 99%
“…The upgrading from VVI to DDD stimulation mode was first proposed in 1992, by Sulke et al, in a randomized study with 16 asymptomatic patients, who had had VVI pacemakers implanted for more than 3 years due to sinus node disease and atrioventricular block. The DDD mode improved the patients' physical capacity and well-being (subjective evaluation), but it was not different from an echocardiographic point-of-view 13 .…”
Section: Discussionmentioning
confidence: 99%
“…This procedure was proposed for the first time in 1992 by SULKE et al, after one randomized study involving 16 asymptomatic patients with VVI pacemakers implanted for more than three years because of sinus node disease and atrioventricular block. The DDD mode offered an improvement in the physical capacity and comfort (subjective evaluation), but it was not different from the echocardiographic point of view [16].…”
Section: Discussionmentioning
confidence: 99%